2006
DOI: 10.1111/j.0889-7204.2006.05782.x
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Interaction of Rifampin and Warfarin

Abstract: Little is known about factors that contribute to either emotional or behavior outcomes following screening for coronary artery disease (CAD). The purpose of this prospective study was to explore these outcomes, along with potentially contributing factors in individuals enrolled in a screening trial for asymptomatic CAD. Included were 47 subjects with type 2 diabetes. Data were collected at study baseline and 3 and 6 months following entry by self-administered questionnaires and telephone follow-up. Emotional o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Other cases and reviews have suggested substantial warfarin dose increases of up 3-to 5-fold may be necessary while on concurrent rifampin therapy. [5][6][7][8][9][10][11] However, in this patient, even a 5-fold dose increase was not sufficient. Our data suggest he may have required a 6-fold or greater warfarin dose increase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other cases and reviews have suggested substantial warfarin dose increases of up 3-to 5-fold may be necessary while on concurrent rifampin therapy. [5][6][7][8][9][10][11] However, in this patient, even a 5-fold dose increase was not sufficient. Our data suggest he may have required a 6-fold or greater warfarin dose increase.…”
Section: Discussionmentioning
confidence: 99%
“…Although this interaction has been long recognized, there exists a paucity of data regarding how to manage such patients. [9][10][11] Various drug information references list this drugdrug interaction as highly significant. Clinical pharmacology suggests that a 2-to 3-fold increase in warfarin dose may be necessary during concurrent therapy to account for this drug-drug interaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore warfarin remains the drug of choice for patient with atrial fibrillation and requiring rifampicin. Several case reports showed challenges and difficulty to achieve therapeutic INR when rifampicin was co-administered with warfarin [4][5][6][7][8]. In addition, there is no published case report in Singapore to show the time course for enzyme induction and de-induction in Asian patient.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly enzyme inhibition can lead to toxicity. The oral anticoagulant warfarin which is metabolized by CYP3A4 and CYP2C9, on concomitant administration with rifampicin has led to therapeutic failure and increased dose requirement . The concomitant administration of amiodarone (inhibitor of CYP2C9 and CYP1A2) with warfarin has led to increased risk of bleeding .…”
Section: Introductionmentioning
confidence: 99%